The effect of proximity to protected areas on community adaptation to environmental change. (1st January 2022) - Gillespie, Josephine; Penny, Dan
Abstract: The consequences of protected areas for proximal human communities are diverse. Protected areas can alleviate poverty by providing a range of economic opportunities for people that live and work within them. Equally, however, they may also disempower and disposes local communities. For communities adapting to systemic environmental change, proximity to protected areas can act to limit potential adaptive pathways. Here, we employ social science methods to explore the impact of an internationally significant protected area on adjacent communities in the Tonle Sap Lake basin, Cambodia. Semi-structured interviews, informed by a scenario framework, reveal an awareness of declining fish yields and a perceived lack of economic alternatives. Vulnerability to hydroclimatic extremes, particularly storms, flood, drought and – increasingly – fire, are exacerbated as a result of proximity to the protected area. We conclude that the impact of protected areas on local communities is heterogenous, and that the development of adaptive and effective management policies requires sensitivity to local conditions and impacts. Highlights: The proximity of resource-dependent communities to protected areas may restrict their adaptive capacity. Fishing communities adjacent to Ramsar wetlands are vulnerable to environmental change. Options for alternative livelihoods are perceived to be limited. Fire is an ascendant natural hazard in seasonal tropical wetlands.